2012
DOI: 10.1371/journal.pone.0032190
|View full text |Cite|
|
Sign up to set email alerts
|

Multimorbidity Patterns in Primary Care: Interactions among Chronic Diseases Using Factor Analysis

Abstract: ObjectivesThe primary objective of this study was to identify the existence of chronic disease multimorbidity patterns in the primary care population, describing their clinical components and analysing how these patterns change and evolve over time both in women and men. The secondary objective of this study was to generate evidence regarding the pathophysiological processes underlying multimorbidity and to understand the interactions and synergies among the various diseases.MethodsThis observational, retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
227
4
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 231 publications
(270 citation statements)
references
References 54 publications
23
227
4
16
Order By: Relevance
“…Así, por ejemplo, hay trabajos 28-30 que han descrito posibles variaciones en la declaración de enfermedades en las encuestas de salud en patologías asintomáticas o con síntomas inespecíficos, aunque se considera que la limitación de la pregunta al año previo puede controlar en parte los sesgos de memoria. En relación al uso de EDC, ha sido previamente empleado sobre todo para el estudio de la multimorbilidad 31,32 , debido a que facilita el manejo y la interpretación clínica de los resultados, al colapsar las diferentes formas de codificación de diagnósticos similares en grupos mutuamente excluyentes.…”
Section: Discussionunclassified
“…Así, por ejemplo, hay trabajos 28-30 que han descrito posibles variaciones en la declaración de enfermedades en las encuestas de salud en patologías asintomáticas o con síntomas inespecíficos, aunque se considera que la limitación de la pregunta al año previo puede controlar en parte los sesgos de memoria. En relación al uso de EDC, ha sido previamente empleado sobre todo para el estudio de la multimorbilidad 31,32 , debido a que facilita el manejo y la interpretación clínica de los resultados, al colapsar las diferentes formas de codificación de diagnósticos similares en grupos mutuamente excluyentes.…”
Section: Discussionunclassified
“…Prados-Torres et al used exploratory factor analysis to identify five patterns of multimorbidity among primary care patients in Spain [23]: cardiometabolic, mechanical, psychogeriatric, depressive, and psychiatric-substance abuse. Each pattern consisted of several chronic conditions that tended to occur together and the authors assigned a name to each cluster based on the types of conditions present.…”
Section: Multimorbidity: Scope Of the Problemmentioning
confidence: 99%
“…2 Although it particularly affects the older population, this problem is also present at other stages of life, including childhood. 3 Recent studies have revealed the existence of patterns of multimorbidity that consist of systematically associated clinical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recent studies have revealed the existence of patterns of multimorbidity that consist of systematically associated clinical conditions. 2 Such patterns evolve and worsen over the course of a patient's life, and reflect clinical situations that cut across individual medical specialties established by healthcare systems. 2 The consequences of this complex reality for a healthcare system in which the majority of illnesses are chronic and affect the older and frailer portion of the population include polypharmacy (that is, the simultaneous and prolonged prescription of multiple medications to a single individual), 4 and repeated referrals for specialised care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation